Niqivut (our food)—dimensions of Inuit country food harvesting and significance in Arctic Canada: bountiful, seasonal, “soul food” - Natalie Ann Carter; Nicolien van Luijk; Jackie Dawson; Colleen Parker; Kayla Grey; Jennifer Provencher; Chantel Emiktaut; Natasha Simonee; Gloria Song; Sonia Wesche (Arctic Science)
Harvesting mammals, fishes, birds, eggs, and plants underpins Inuit culture across Inuit Nunangat (Inuit homeland in Canada). Climatic and nonclimatic drivers affect Inuit access to these items and have cascading effects on social determinants of Inuit health. A holistic understanding of the diversity and seasonality of harvesting is needed to support Inuit food sovereignty and security. Our goals were (a) to develop a broader understanding of the diversity and seasonality of harvesting country food across varied geographic contexts in Arctic Canada, and (b) further document the significance and benefits of country food as part of Inuit food sovereignty and systems across a range of communities. Knowledge holders in 14 communities spanning three Inuit regions shared knowledge and perspectives surrounding species harvested seasonally and species’ significance. Results demonstrate the range of overlapping yet diverse country food systems across Inuit regions, the seasonality and temporality of harvesting, and include a “survey” of species related to Inuit culture. This study highlights the cultural significance and benefits (nutritional, medicinal, mental health, connection to culture, and language) of country food; and reinforces that harvesting, processing, sharing, and eating country food are fundamental aspects of Inuit culture, wellbeing, and food sovereignty.